The relationship between organizational culture and teamwork / Nuryusrina Yusri - Yusri, Nuryusrina (Faculty of Business and Management, 2018)
Working in teams has become relevant in any organization today and it can be achieved through the coordination of both team members and tasks to be done. Teamwork also demonstrates improved work quality and guidance to achieve better results from individual work steps. The main objective is to identify the relationship between organization culture and teamwork at Lembaga Pertubuhan Peladang Negeri Melaka. A cluster sampling technique was used to get a sample 66 from total population 80 employees. The data obtained was processed using Statistical Package for Social Sciences (SPSS) Version 21 and was analyzed using reliability test, validity test, frequency distribution, descriptive analysis, Pearson’s correlation coefficient and multiple regression analysis. This research found that individualism, power distance, uncertainty avoidance and masculinity has negative relationship toward teamwork. This study recommended that LPP Melaka should increase culture collective and low power distance in teamwork by any programs.